Spend Now, Pay Later? : Tax Smoothing and Fiscal Sustainability in South Asia. (IMF Working Papers; Working Paper ;, 1999)
This paper tests a version of Barro's tax-smoothing model, which assumes intertemporal optimization by a government seeking to minimize the distortionary costs of taxation, using Pakistan and Sri Lankan data for 1956-95 and 1964-97, respectively. The empirical results indicate that Pakistan's fiscal behavior is consistent with tax smoothing, but not Sri Lanka's. Moreover, fiscal behavior in both countries was dominated by a stagnation of revenues, large tax-tilting-induced deficits, and the consequent accumulation of excessive public liabilities. Analysis of the time-series characteristics of tax-tilting behavior indicates that for both countries the stock of public liabilities is unsustainable under unchanged fiscal policies.